The Differences Overlap Camshaft Duration to Performance Motorcycle 4- Stroke 110cm3 - Nurfirmansyah, Muhammad; Ahmad Hanif Firdaus (Formosa Journal of Science and Technology, 2024)
The loss of performance in a motorcycle that has been used for a long time makes it uncomfortable when used. The purpose of this research is to determine the results of the effect of camshaft overlap duration on the performance of a 110 cc petrol engine. To verify its performance, experimental research methods were used in this thesis research. The research results show that variations in camshaft overlap duration between 12o, 15o, 18o (standard) 23o, and 28o have the effect of increasing vehicle performance. For example, using a variation of camshaft overlap duration of 28o produces the highest torque of 7,82 (Nm) at an engine speed of 6500 rpm and the highest power of 7.45 (Hp) at an engine speed of 7000 rpm and produces maximum BMEP 909,96 (KPa) at engine speed 6500 rpm. This can happen because according to the theory the greater the camshaft overlap duration on a vehicle, the better the flushing of the combustion chamber at top speed.